صعوبة معالجة المعلومات وعلاقتها باتخاذ القرار لدى مدراء مدارس التعليم الأساسي بسلطنة عمان - خروصي، خالد علي
This study aimed to identify the relationship between information processing and decision-making among a sample of school principals in the General Directorate of Education in the Al-Batinah South Governorate in the Sultanate of Oman, and their obstacles and ways to improve them from the workers' point of view. In addition to knowing whether there are statistically significant differences at the level of significance (0.05 ≥ α) between the averages of the study sample's scores in decision-making and its dimensions for the variables (gender -years of experience- academic qualification- job title). In this study, the researcher relied on the descriptive and comparative approach to apply the study tools to the sample and to reveal their effect on the dependent variables, because it is used in the comparison between two or more phenomena (processing information in relation to decision-making), to arrive at results about the studied phenomena or problems as possible from Plan it for the future. The researcher used two main tools, which are the decision-making scale, and the information-processing style scale (prepared by the researcher). Benefiting from access to research and studies in the same fields. The study sample consists of all school leaders (males and females) from the pre-university education schools of the General Directorate of Education in the Governorate of South Al Batinah in the Sultanate of Oman; their number is (137). The study concluded -in its entirety- that there is a correlation between the pattern of information processing and the ability to make decisions. It follows from this that the interpretation of individual differences in decision-making and in various mental abilities far exceeds the differences in the pattern of information processing. The study is expected to benefit centers and institutions preparing school leaders in raising the capacity for creative thinking and decision-making and enabling them to read and process statistical data and indicators to benefit in decision-making.